แรงจูงใจและกลวิธีเชิงพฤติกรรมการป้องกันต่อการดื่มแอลกอฮอล์ของนักศึกษาอาชีวศึกษาในจังหวัดเชียงใหม่ - ภัคจิรา ภูสมศรี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The study was a descriptive study carried out to motive and protective behavioral strategies on alcohol drinking of the vocational students in Chiang Mai. Data collection was conducted by using self-administered questionnaire among 353 Vocational Students. Data were analyzed using descriptive statistic, percent, mean, standard deviation, chi-square test, and Pearson’s product moment correlation. The findings of this study are summarized as follows: 1) Almost 80.7 % of vocational student had drunk alcohol. Most of student aged 14 or 15 years had drunk alcohol in the first time. Most favorite alcohol beverage was beer at (70.2 %). Most of student 56.1% had drunk alcohol once or twice a year. They would drink heavily until they got drunk each time. The main reason for drinking alcohol was curiosity to taste at 59.3% 2) The overall of drinking motive moderate degree was correlation with alcohol use (r=0.530). Consideration a list aspects of drinking motives, social motive, coping with problems motives, enhancement motives, and conformity motives were significantly associated with alcohol use moderate degree of correlation with alcohol use (r = 0.430 - 0.530) 3) The overall of Protective Behavioral Strategies low degree was correlation with alcohol use (r=0.278). Consideration a list aspects of Protective Behavioral Strategies found that stopping/limiting drinking, manner of drinking were significantly associated with alcohol use. Serious negative consequences no significant correlations with alcohol use. Protective Behavioral Strategies drinking low degree was correlation with alcohol use (r = 0.067 - 0.430)